Unmet Needs in Children With Attention Deficit Hyperactivity Disorder—Can Transcranial Direct Current Stimulation Fill the Gap? Promises and Ethical Challenges - Sierawska, Anna; Prehn-Kristensen, Alexander; Moliadze, Vera; Krauel, Kerstin; Nowak, Rafal; Freitag, Christine M.; Siniatchkin, Michael; Buyx, Alena (Frontiers in Psychiatry, 2019)
Attention deficit hyperactivity disorder (ADHD) is one of the most frequent disorders in children and adolescents. Although ADHD can be effectively treated with psychostimulants, a significant proportion of patients discontinue treatment because of adverse events or insufficient improvement of symptoms. In addition, cognitive abilities which are frequently impaired in ADHD, are not directly targeted by medication. Therefore, additional treatment options, especially to improve cognitive abilities, are needed. Because of its relatively easy application, well established safety and low cost, transcranial direct current stimulation (tDCS) is a promising additional treatment option. Further research is needed to establish efficacy and to integrate this treatment into the clinical routine. In particular, limited evidence regarding the use of tDCS in children, lack of clear translational guidelines and general challenges in conducting research with vulnerable populations pose a number of practical and ethical challenges to tDCS intervention studies. In this paper, we identify and discuss ethical issues related to research on tDCS and its potential therapeutic use in ADHD in children and adolescents. Relevant ethical issues in tDCS research for pediatric ADHD center on safety, risk/benefit ratio, information and consent, labelling problems, and non-medical use. Following an analysis of these issues, we develop a list of recommendations that can guide clinicians and researchers in conducting ethically sound research on tDCS in pediatric ADHD.